ERGONOMICS DESIGN ANALYSIS TOWARDS GAMERS’ PREFERENCES IN COASTAL ESPORTS ARENA - Leonardo, Leonardo; Suwarlan, Stivani Ayuning; Aguspriyanti, Carissa Dinar (MODUL, 2023)
Esports activities are developing very rapidly, encouraging the people’s desire to build its distinctive building, an esports arena to support its activity. However, there is no specific spatial form for planning the main room’s interior of esports arena, especially in coastal areas. The absence of guidelines to be applied can lead to less ergonomic spatial planning. This research applies the mixed descriptive method by collecting primary data of questionnaire and secondary data of existing buildings from any official information source as the object of research analysis. With digital information source, source triangulation method is used to identify an ergonomic layout and furniture form to be used by the player and audience within the esports arena building in the coastal zone. The result of this study provides an overview of ergonomic layout and furniture form that can be applied to planning the coastal esports arena building.